Comparison of additive manufactured models of the mandible in accuracy and quality using six different 3D printing systems - Gottsauner, Maximilian; Reichert, Torsten E.; Koerdt, Steffen; Wieser, Stefan; Klingelhöffer, Christoph; Kirschneck, Christian; Hoffmann, Jürgen; Ettl, Tobias; Ristow, Oliver (Journal of cranio-maxillofacial surgery, 2021)
The aim of this study was to analyze and compare the accuracy and quality of six 3D printing systems available on the market. Data acquisition was performed with 12 scans of human mandibles using an industrial 3D scanner and saved in STL format. These STL files were printed using six different printing systems. Previously defined distances were measured with a sliding caliper on the 72 printed mandibles. The printed models were then scanned once again. Measurements of volumes and surfaces for the STL files and the printed models were compared. Accuracy and quality were evaluated using industrial software. An analysis of the punctual aberration between the template and the printed model, based on a heat map, was also carried out. Secondary factors, such as costs, production times and expendable materials, were also examined. All printing systems performed well in terms of accuracy and quality for clinical usage. The Formiga P110 and the Form 2 showed the best results for volume, with average aberrations of 0.13 ± 0.23 cm3 and 0.12 ± 0.17 cm3, respectively. Similar results were achieved for the heat map aberration, with values of 0.008 ± 0.11 mm (Formiga P110) and 0.004 ± 0.16 mm (Form 2). Both printers showed no significant difference from the optimal neutral line (Formiga P110, p = 0.15; Form 2, p = 0.60). The cheapest models were produced by the Ultimaker 2+, with an average of 5€ per model, making such desktop printers affordable for rapid prototyping. Meanwhile, advanced printing systems with sterilizable and biocompatible printing materials, such as the Formiga P110 and the Form 2, fulfill the high expectations for maxillofacial surgery.